2018
DOI: 10.1155/2018/3408089
|View full text |Cite
|
Sign up to set email alerts
|

Presumptive Treatment of Malaria in Ghana: Was It Ever Useful? Evidence from the Kassena-Nankana District of Northern Ghana

Abstract: Background The WHO currently advocates parasitological confirmation of malaria before treatment is commenced. However, many arguments have emerged both for and against this new position. To contribute to the debate, this secondary data analysis was conducted to determine the likelihood of malaria parasitaemia in a child presenting with fever, vomiting, or cough in the Kassena-Nankana District. Methods The dataset for this analysis was generated during a study to assess the incidence and risk factors for paedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Similarly, in Ghana, fever is the most common symptom that often leads to presumptive treatment. 35 As in the current study, in Ethiopia, continued customer pressure was the major reason for maintaining the counter-sale of antibiotics. 46 Similar to our study, client pressure has been identified as a factor behind dispensing antibiotics among community pharmacists in Sudan.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Similarly, in Ghana, fever is the most common symptom that often leads to presumptive treatment. 35 As in the current study, in Ethiopia, continued customer pressure was the major reason for maintaining the counter-sale of antibiotics. 46 Similar to our study, client pressure has been identified as a factor behind dispensing antibiotics among community pharmacists in Sudan.…”
Section: Discussionmentioning
confidence: 63%
“…2 Treating malaria without prior diagnostic confirmation promotes self-medication, which can lead to antimalarial resistance, a global concern. [34][35][36][37] Thus, this finding illustrates a potential risk of malaria misdiagnosis, which may accelerate the burden of antimalarial drug resistance reported in Rwanda as the first African country. 21 The current finding is yet another demonstration that those community pharmacies facilitate self-medication, which was similarly reported in a study in Rwanda.…”
mentioning
confidence: 75%
“…Additionally, donors that did not use insecticide repellents and those that were nocturnally active for a long time as well as those that experienced frequent mosquito bites were associated with subclinical malaria. The factors identified in this study have previously been identified to be associated with clinical malaria [ 19 25 ]. These findings were not surprising since all clinical malaria cases begin asymptomatically.…”
Section: Discussionmentioning
confidence: 98%
“…The hazard of presumptive treatment hence is not just overdiagnosis of malaria, but also confusion and subsequently missed opportunities to correctly treat an ill child. Certain relevant studies [ 6 , 7 ] demonstrated that patients with symptoms similar to malaria in endemic areas should not always be treated as malaria without laboratory confirmation. Presumptive treatment can indirectly accelerate the emergence of parasite resistance [ 8 ] to treatment, resulting in nonmalarial fevers being inappropriately treated with antimalaria drugs, endangering patient life and quality of care.…”
Section: Introductionmentioning
confidence: 99%